(4aS,4bR,7R,10aS)-3,7-Dimethyl-10a-(propan-2-yl)-1,4,4a,4b,5,6,7,8,10,10 a-decahydrophenanthrene-1,4-dione - Caracelli, I.; Zukerman-Schpector, J.; Lousada Machado, A.T.; Brocksom, T.J.; Lucia Ferreira, M.; Tiekink, E.R.T. (International Union of Crystallography, 2011)
In the title compound, C(19)H(26)O(2), the A ring adopts a chair conformation, whereas the B and C rings both adopt distorted half-chair conformations with the quaternary C atom common to both rings lying 0.577 (3) and 0.648 (3) angstrom out of the approximate plane defined by the remaining five C atoms (r.m.s. deviations = 0.1386 and 0.1156 angstrom) for the B and C rings, respectively. Molecules are assembled in the crystal through C-H center dot center dot center dot O interactions involving both carbonyl O atoms, which lead to supramolecular chains aligned along the b axis.